Determinants of profit efficiency among smallholder beef producers in Botswana - Bahta, Sirak T.; Baker, Derek (2015)
The livestock sector is vital to Botswana’s rural economy comprising nearly two-thirds to the national agricultural sector. The goal of this research is to measure competitiveness and identify the factors affecting it, so as to advocate change in Botswana’s smallholder livestock systems. The study examines a cross section of farm - level data gathered from 556 randomly selected livestock producers to investigate the profit efficiency and competitiveness of three farm size categories of small holder livestock farmers. Results found a considerable capacity to improve beef profitability. Scale effects on profit efficiency are generally positive, but the results indicate a number of interactions between scale and other variables such as off-farm income and the use of credit. Policy analysis and commercial decisions using models that assume efficiency are therefore presenting a misleading picture, particularly on the elusive subject of Botswana smallholders’ beef supply response.